Perbandingan pengaruh bola standar dan bola modifikasi terhadap kemampuan dribble sepakbola - Jatmiko, Setia Dwi; Harmono, Setyo; Atrup, Atrup; Mashuri, Hendra (Universitas Tanjungpura, 2022)
The purpose of this study was to compare the use of ball facilities to develop soccer dribbling skills. The facilities used are standard balls and plastic balls. The method of this research is experimental with pre-test post-test group design. The research subjects were extracurricular students at SD Negeri 1 Kendal, Tulungagung, totaling 30 students. The research instrument used the Rogalski Degel Soccer Dribbling Test. The results showed significant development of dribbling ability using standard balls and plastic balls. However, the use of plastic balls gave a better effect than the use of standard balls for elementary school-aged students.